A dominant negative mutant of microphthalmia transcription factor (MITF) lacking two transactivation domains suppresses transcription mediated by wild type MITF and a hyperactive MITF derivative - Vachtenheim, Jiri; Drdová, Blanka (Pigment cell research, 2004)
Microphthalmia transcription factor (MITF) positively regulates transcription of differentiation-related genes in several cell lineages, including melanocytes. Recent data also indicate a new important role for MITF as a factor that appears to be required for survival of melanoma cells, suggesting a possibility that abrogation of MITF function in transformed melanocytes could lead to a decreased survival via attenuating anti-apoptotic signals. Therefore, to gain a better understanding of the role which MITF plays in melanoma cell survival, it is important to find efficient means of abolishing the transactivation of its target genes. Recently, a dominant negative MITF lacking the N-terminus has been shown to down-regulate tyrosinase and Trp1 expression in normal melanocytes and mouse B16 melanoma cells. Here, a dominant negative mutant of the melanocyte-specific isoform of MITF is described carrying deletions of both N- and C-terminal transactivation domains. Cotransfection of this mutant resulted in a complete inhibition of the wild type MITF function as tested on both the reporter-linked tyrosinase promoter and an endogenous, ectopic MITF-triggered tyrosinase gene in U2-OS cells. The dominant negative construct also strongly repressed the activity of a hyperactive MITF-Vp16 chimera. Importantly, deletion of both activation domains was necessary to eliminate the residual transcription activity observed when only the N-terminal domain was removed and to achieve the repressive effect in human melanoma cells. If the activity of MITF plays a role in the long-term survival of malignant melanocytes, overexpression of a strong dominant negative MITF mutant might be a useful strategy to suppress its transactivation function.
Keywords: umělá fúze genů; aktivace transkripce; Recombinant Proteins; suprese genetická; Herpes Simplex Virus Protein Vmw65; Cell Line, Tumor; DNA-Binding Proteins; Protein Structure, Tertiary; terciární struktura proteinů; Transcription, Genetic; herpes simplex virus - protein Vmw65; Gene Expression Regulation, Enzymologic; tyrosinasa; Transcriptional Activation; promotorové oblasti (genetika); DNA vazebné proteiny; Monophenol Monooxygenase; genetická transkripce; rekombinantní proteiny; dominantní geny; Animals; lidé; Transcription Factors; Genes, Dominant; transkripční faktory; Humans; regulace genové exprese enzymů; zvířata; Promoter Regions, Genetic; myši; Artificial Gene Fusion; Microphthalmia-Associated Transcription Factor; nádorové buněčné linie; Mice; virové geny; Suppression, Genetic; transkripční faktor spojený s mikroftalmií; Genes, Viral